Pengembangan Multimedia Pembelajaran Fisika Menggunakan Swish Max 4.0 pada Materi Cahaya Kelas VIII Madrasah Tsanawiyah - sari, ayu permata; aswirna, prima; nurhasnah, nurhasnah (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Physics has an abstract concept and is not easily attributed to everyday events in human life, making it difficult to imagine. If the physical phenomenon being discussed has ever been experienced by learners may learners will be able to reconstruct it back into a better understanding and vice versa. Efforts to overcome every problem in physics learning along with changes in educational communication technology in the form of utilization of learning media using a computer one of them using software swish max 4.0. The purpose of this research is to develop physics learning multimedia using swish max 4.0 on class VIII Madrasah Tsanawiyah materi cahaya that is valid, practical and effective. The benefits of physics learning multimedia developed is as a medium of learning for educators in delivering related material, and can help in creating a fun learning atmosphere and increase learning interests of learners. Research and development using 4-D model, starting from define, design, development and disseminate. Test the validity of multimedia physics learning using validity questionnaires, practicality test using questionnaire of practice and effectiveness test using effectiveness questionnaire. The results showed that physics learning using swish max 4.0 in materi cahaya class VIII MTsN Durian Tarung Padang very valid, very practical and effective.